Reasons, Barriers, and Consequences of Divorce in Female Victims of Violence - Mestvirishvili, Maia; Kvitsiani, Mariam; Mestvirishvili, Natia; Tsomaia, Tina (Georgian Psychological Journal, 2026)
Gender-based violence is one of the most widespread forms of human rights violation. It often occurs in societies, including Georgia, where women have less social and economic influence. Despite the steps taken over the past decade to combat gender-based violence, femicide, as the most severe form of gender violence, remains alarming. Analysis of femicide cases shows that women are often murdered by their husbands, partners, or former partners, which indicates that ending violent relationships (divorce) poses increased risks for women. The aim of the study is to analyze socio-cultural and structural factors that (1) influence the decision of female victims of violence to divorce, (2) create barriers in the process of divorce, and (3) increase the risk of violence after relationship termination. The study involved 12 in-depth interviews with female victims of violence and 4 interviews with the policy paper developers. The results showed that most women identify themselves as victims of violence belatedly, which is linked to socio-cultural norms and stigma. Women’s silence and fear of anticipated danger hinder help-seeking; institutional barriers and societal attitudes further complicate the situation. After divorce, women often remain isolated and under increased threat from former partners. The findings suggest that preventing gender-based violence requires a comprehensive approach that considers socio-cultural, legal, and psychological factors.